Mortality patterns in the Russian Federation: indirect technique using widowhood data - Bobak Martin; Murphy Michael; Pikhart Hynek; Martikainen Pekka; Rose Richard; Marmot Michael (The World Health Organization, 2002)
OBJECTIVE: The Russian mortality crisis of the early 1990s attracted considerable attention, but information on possible covariates of mortality is lacking, and concerns have been raised about the validity of official mortality data. To help elucidate the determinants of mortality, we examined whether indirect demographic techniques could be used to study mortality in countries such as the Russian Federation, where mortality data are inadequate, using input data independent from official vital statistics. METHODS: A national sample of the population was interviewed (n = 1600, response rate = 67%). Participants who had ever been married (82% of the sample) were asked about the date of birth and vital status of their first spouse. Spousal mortality was then estimated indirectly for the 531 men and 710 women for whom valid data were available. FINDINGS: The estimated risk of death between the ages of 35-69 years was 57% for male spouses and 17% for female spouses. Corresponding figures derived from national data for 1990 were 52% and 25% for the Russian Federation, and 31% and 20% for the United Kingdom. According to spouses' reports, 38% of their husbands died from cardiovascular disease, 22% from cancer, and 14% from injuries and accidents. Mortality of male spouses was inversely related to the education level of their wives, and the age-adjusted hazard ratios for death from all causes, compared to primary education, were 0.77 for secondary education and 0.57 for university education (trend P = 0.03). Mortality was also inversely related to ownership of household items, but not to size of settlement, pride in Russia, membership in the Soviet Communist Party, nationality or self-assessed social status. CONCLUSIONS: Although the indirect estimates were imprecise (partly owing to the small population size of the study), and mortality in women was probably underestimated (owing to many factors, including poorer reporting by males and high male mortality), our results are nevertheless consistent with the mortality pattern observed in official mortality data. The indirect technique thus appears to be a useful tool to study the determinants of mortality in the Russian Federation and other populations, where reliable or sufficiently extensive data are not available.